Hukum Islam Dan HAM: Tinjauan Hukum Poligami dan Kesetaraan Hak dalam Perkawinan - M Ali Mubarok; Dety Vera Dinyati (Indonesia, 2023)
The Declaration of Human Rights (HAM) in 1948 by the General Assembly of the United Nations (UN) has become a reference for the international community and has influenced aspects of international law. However, the interpretation of human rights and their implementation within the national scope often clashes with local culture and laws. As Islamic law is codified in various Muslim countries which are also part of the United Nations. Is there a conflict between International Human Rights Law and Islamic Law then what is the solution, also how is the harmonization between Islamic Law and Human Rights regarding the permissibility of the practice of polygamy which violates the Principle of Equality is a question that must be answered thoroughly from the perspective of both. The dialogical approach finds answers that are very relevant, through the rule of "Mashlahah", Islamic law and international human rights can dialogue in order to reach a common understanding in order to realize human rights in the Muslim world. By utilizing women's legal rights, namely "ta'liq al-thalaq and tafwidh al-thalaq" or the marriage agreement in the marriage contract not to be polygamous, the practice of polygamy becomes everyone's "free choice". In the Indonesian context, it is regulated in Law no. 1 of 1974 concerning Marriage Chapter V Article 29, and Compilation of Islamic Law (KHI) Chapter VII Articles 45-52. The marriage agreement is also listed in the Counter Legal Draft Chapter V Articles 21 and 22. This is in accordance with Islamic Law and also fulfills the obligations of Muslim countries to guarantee equal rights in marriage.